INVESTIGATING THE THERAPEUTIC POTENTIAL OF FICUS DELTOIDEA JACK IN THE MANAGEMENT OF DIABETES MELLITUS: A COMPREHENSIVE REVIEW OF PHYTOCHEMISTRY, PHARMACOLOGY, AND CLINICAL EVIDENCE IN MALAYSIA - Al-Mahdi, Aisha Fatima (Global Journal of Medical and Health Science, 2023)
Diabetes Mellitus (DM) is a global health concern, and the search for effective natural remedies has led to the exploration of indigenous plants like Ficus deltoidea Jack (FDL) in Malaysia. This comprehensive review examines the therapeutic potential of FDL in managing diabetes, encompassing phytochemistry, pharmacology, and clinical evidence. FDL is a native Malaysian plant rich in bioactive compounds, including flavonoids, phenols, and alkaloids. These phytochemicals are known for their anti-diabetic properties, making FDL a promising candidate for diabetes management. The pharmacological studies highlighted in this review demonstrate the various mechanisms through which FDL exerts its anti-diabetic effects. These mechanisms include enhancing glucose uptake in cells, inhibiting α-glucosidase and α-amylase activities, and reducing postprandial hyperglycemia. Additionally, FDL has shown anti-inflammatory and antioxidant properties, which are vital in mitigating diabetic complications. The clinical evidence discussed in this review corroborates FDL’s anti-diabetic potential. Studies conducted in Malaysia have revealed that FDL extracts can effectively lower blood glucose levels, making it a valuable adjunct therapy for diabetes patients. Furthermore, FDL has demonstrated anti-inflammatory and anti-oxidant effects, which can contribute to better diabetes management and reduced risk of complications. In conclusion, Ficus deltoidea Jack holds significant promise as a natural therapeutic agent for diabetes mellitus management. Its phytochemistry, pharmacological actions, and clinical evidence support its use as an adjunct therapy to help control blood glucose levels and mitigate the complications associated with diabetes. Further research and clinical trials are warranted to explore FDL’s full potential and to establish it as a safe and effective option for diabetes management in Malaysia and beyond